The Potential of the Volumetric Sphygmography for the Diagnosis of Impaired Arterial Stiffness in Patients with Uncomplicated Arterial Hypertension and Its Possibilities for Evaluation of the Antihypertensive Therapy Effectiveness - E. V. Borisova; A. I. Kochetkov; O. D. Ostroumova (Столичная издательская компания, 2018)
Aim. To investigate arterial stiffness parameters in middle-aged patients with stage II grade 1-2 essential arterial hypertension (HT) and evaluate their changes after treatment with single pill combinations (SPC) of antihypertensive drugs.Methods. At the first phase  of the study, according to the medical records data, a group of untreated patients with stage II grade 1-2  HT (n=100, 47 men, mean age 51.9±6.5 years), and a group of healthy controls with normal blood pressure (BP) (n=86; 28 men; mean age 48.8±5.8 years) were formed. The analysis of arterial stiffness was performed by the volumetric sphygmography technique using VaSera VS-1500N device (Fukuda Denshi Co., Ltd, Japan). All the subjects underwent ambulatory BP monitoring (BPLab, BP2005-01.04.00.2540, Petr Telegin, Russia) as well as a routine BP measurement by the Korotkov method. At the second  stage  of the study, a group of HT patients (n=90) was formed  according to the medical history data.  These patients thanks  to antihypertensive treatment with SPC (perindopril arginine/indapamide or valsartan/amlodipine) achieved the target BP level (<140/90 mm Hg) according to routine measurements and they were assessed in terms  of therapy efficacy (general clinical data, SMAD, volume sphygmography) 12 weeks after the target BP level was reached.Results. At the first phase of the study, in HT patients cardio-ankle vascular index (CAVI), both on the left (7.9±1.3) and right side (8.1±1.3), as well as the right-side augmentation index (1.22±0.31%) were significantly higher (p=0.006, p=0.003, p=0.047, respectively) compared to the controls (7.5±0.9, 7.6±0.9, 1.13±0.28%, respectively). At the second  phase  of the study, after SPC treatment the CAVI significantly decreased both on the left- (up to 7.36±1.37, p=0.02) and right-side (up to 7.46±1.44, p=0.02).Conclusions. In untreated 40-65 years-old patients with stage II grade 1-2 HT arterial stiffness assessed by volumetric sphygmography is significantly higher compared with sex-matched healthy individuals. 12-week therapy with SPCs improves the elastic properties of the major arteries, reducing the CAVI value.